ROLE OF PROBIOTICS IN GASTROINTESTINAL TRACT DISEASES: INFLAMMATORY BOWEL DISEASE AND NECROTIZING ENTEROCOLITIS - SHUKLA, SHATAKSHI; VERMA, SALONI; SHARMA, REKHA; KUMARI, ANKITA; ADLINGE, RAHUL (International Journal of Current Pharmaceutical Research, 2021)
Bacterial microflora which is present in gastrointestinal tract cause various disorders. Probiotics provides beneficial effects in gut related disease. Previously probiotics are used as alternative medicine but now entering in mainstream medicine. Probiotics help in restoring normal bacterial microflora and regulate the gastrointestinal tract functioning through different mechanisms. There are only few evidences available which show potential benefits of probiotics. The efficiency of probiotics used as a single strain or multiple formulation is tested in various diseases such oral health, diabetes, multiple sclerosis, inflammatory bowel disease, necrotising enterocolitis and many more. The purpose of this paper is to focus on diseases related to gastrointestinal tract including inflammatory bowel disease and necrotising enterocolitis based on the literature review available and propose future perspective to reduce the translocation of bacterial microflora in gastrointestinal tract and reducing subsequent inflammation of gut. Keywords were searched in goggle scholar, academic research, PubMed and Embase databases.